Potential strategies to reduce inappropriate prescribing and dispensing of antimicrobials in Bangladesh building on the experiences in other developing countries - Haque, Mainul; Godman, Brian (Bangladesh Journal of Medical Science, 2021)
Abstract not available Bangladesh Journal of Medical Science Vol.20(4) 2021 p.700-706